A catastrophic antiphospholipid syndrome complicated with heparin-induced thrombocytopaenia, successfully managed with double filtration plasmapheresis, steroids and a direct thrombin inhibitor. Issue 9 (16th September 2019) - Prouvot, Julien; Aglaé, Cédric; Daniel, Laurent; Moranne, Olivier
Abstract : A middle-aged woman with history of antiphospholipid syndrome, admitted to our hospital for lethargy and persistent chest pain, developed during hospitalisation intracerebral transverse sinus and sigmoid vein thromboses, retinal thromboses, acute renal failure and cardiac involvement associated with thrombocytopaenia. Diagnosis of catastrophic antiphospholipid syndrome was made and treated with IV steroids, heparin infusion and double filtration plasmapheresis (DFPP) without fresh frozen plasma. Heparin-induced thrombocytopaenia was second diagnosed because of persistent severe thrombocytopaenia after 2 weeks of treatment associated with positive conversion of antibodies against platelet factor 4, and a positive functional assay. The clinical course was complicated by cerebellar haematomas that appeared a few days after the last session of DFPP. Heparin-induced thrombocytopaenia was managed by administration of argatroban, a direct thrombin inhibitor with an increase in platelet count. Neurologically, the patient recovered completely and was discharged on vitamin K antagonist treatment and regular dialysis.